Secukinumab administration by autoinjector maintains reduction of plaque psoriasis severity over 52 weeks: results of the randomized controlled JUNCTURE trial. (23rd January 2017) - Lacour, J.‐P.; Paul, C.; Jazayeri, S.; Papanastasiou, P.; Xu, C.; Nyirady, J.; Fox, T.; Papavassilis, C.
Abstract: Background: User satisfaction is an important factor associated with treatment adherence in chronic diseases including moderate‐to‐severe psoriasis. Objective: To evaluate the efficacy, safety and patient acceptability of 300 and 150 mg secukinumab – a fully human anti‐interleukin‐17A monoclonal antibody that has demonstrated efficacy in the treatment of patients with moderate‐to‐severe plaque psoriasis – self‐administered by autoinjection. Methods: Patients with moderate‐to‐severe plaque psoriasis were randomized to secukinumab 300 mg, secukinumab 150 mg or placebo self‐administered by autoinjection at baseline, Weeks 1, 2 and 3 and then every 4 weeks from Week 4 to Week 48. Efficacy responses [≥75/90/100% improvement in Psoriasis Area and Severity Index (PASI 75/90/100) and clear/almost clear skin by Investigator's Global Assessment 2011 modified version (IGA mod 2011 0/1)] were measured at Week 52. Patient‐reported usability of the autoinjector was evaluated by the self‐injection assessment questionnaire to Week 48. Results: At Week 52 with secukinumab 300 mg, PASI 75/90/100 and IGA mod 2011 0/1 responses were achieved by 81.4/64.1/38.8% and 69.6% of patients, respectively, by multiple imputation. At Week 52 with secukinumab 150 mg, PASI 75/90/100 and IGA mod 2011 0/1 responses were achieved by 75.2/57.4/33.1% and 60.2% of patients, respectively, by multiple imputation. Patient‐assessed acceptability of the autoinjector remained high to Week 48. The proportion of patients experiencing adverse events was greater with secukinumab 300 mg (88.6%) than with secukinumab 150 mg (78.7%). Conclusion: Self‐administration of secukinumab using an autoinjector was associated with robust and sustained efficacy, a good safety profile and high acceptability.